Annual Plan 1993-94 Review and Outline - Planning Commission (Planning Commission, 1992)
The tiny of Manipur with an area of only 22,327 sq.km, is situated in the easternmost fringe of the country. It is surrounded by Myanmar on the east, Nagaland on the north, Assam on the west and Mizoram on the south. the total boundary line is about 934 kms. of which 352 kms. line lies on Indo-Myanmar International Border. It has a salubrious climate, exotic greenery and rich flora and fauna besides the rich culture. During the Second World War the marching Japanese forces described it as "Lotus on the Lofty Hill" and late Pt. Jawaharlal Nehru described as "Jewel of India".
Planning Department